Chitosan-phenylalanine-mPEG nanoparticles: From a single step water-based conjugation to the potential allergen delivery system. (5th May 2016) - Jirawutthiwongchai, Jatesuda; Klaharn, I-yanut; Hobang, Nattapat; Mai-ngam, Katanchalee; Klaewsongkram, Jettanong; Sereemaspun, Amornpun; Chirachanchai, Suwabun
Graphical abstract: Highlights: Single step conjugation of chitosan (CS) in water at room temperature is proposed. Chitosan nanoparticles (CS conjugated with Phe and mPEG) can be obtained. The chitosan nanoparticles can immobilize house dust mite allergen (HDM) extract. HDM-chitosan nanoparticles show biocompatibility and immune response inducibility. Abstract: The chemical modification to obtain biocompatible chitosan (CS) nanoparticles for the application in biological system is still on expectation. By simply mixing CS with hydroxybenzotriazole (HOBt), the CS aqueous solution obtained allows a successful single step conjugation of both hydrophobic biomolecules, i.e. phenylalanine (Phe), and hydrophilic polymers, i.e. poly(ethylene glycol) methyl ether (mPEG), on CS, in water at room temperature. The CS-Phe-mPEG nanoparticles (20–50 nm) exhibit positive charge leading to an entrapment of negatively charged house dust mite allergen (HDM) extract ( Dermatophagoides pteronyssinus ). The HDM-entrapped CS-Phe-mPEG shows biocompatibility as evidenced from the cell viability, the ROS (reactive oxygen species) reduction, and the HaCaTs proliferation. The clinical implementation on the healthy- and HDM-allergic volunteers indicates that the HDM-entrapped CS-Phe-mPEG stimulates cell-mediated immune response in peripheral blood mononuclear cells (PBMCs) and favors T cell immune response as seen from the reduction of interferon-(IFN)-γ and interleukin-(IL)-10 in the PBMCs of the HDM-allergic volunteers.